New Contributions to the Archaeological Topography of the Dugopolje Region (Archaeologia Adriatica, 2007)
This article presents the results of archaeological excavations at the site Dugopolje – Vučipolje, along the course of the Zagreb-Dubrovnik highway. Excavation was carried out by the Department of Archaeology of the University of Zadar from February to May 2005. Minor excavations had already been performed at this site in 1980, with the discovery of a walled grave vault from the period of late Antiquity lined with 7 Roman stelae dated to the early Imperial period (CAMBI 2000). The new excavations were intended to uncover a broader context for this grave vault, and were divided into three sectors.The first sector (Fig. 1 and 2) contained a small natural depression that was assumed to have been a pool that was filled during the late Roman/late Antiquity period, as was confirmed by archaeological material dated from the 4th to 6th centuries (Pl. 1 and 2). Immediately next to the above grave vault (Gr. 2), another walled grave vault was discovered (Gr. 1), in which two phases of burial were established (Fig. 3 and 4). The first phase consisted of a burial of a young female in a grave covered by tiles (Gr. 1/II), dated according to the grave goods to the second half of the 4th century (Pl. 3). The later phase consisted of a burial dated according to grave goods and finds to the 6th century (Gr. 1/I) (Pl. 4). The great devastation to the upper part of the grave vault meant that we were not able to establish fully its appearance, but it is hypothesized that it belonged to the type of walled grave vaults with slab roofing, without frontal access. This type of grave vault, like the type of grave vault discovered in 1980 (a walled grave vault with roofing slabs and a frontal access area), are characteristic for cemeteries of the 3rd to 6th centuries. The grave goods indicate the transformation that occurred in the beliefs of the members of the corresponding community, as the deceased woman from Gr. 1/II was buried according to pagan ritual (a vessel on the chest), while the later burial was of a member of a Christian community, as shown by the image of a cross on a ring. Sector 2 was located in the immediate vicinity of the excavated grave vaults (Fig. 1 and 2), and it belonged to the settlement complex related to the grave vaults. Excavation was undertaken in the area where the geo-radar investigative method showed the densest concentration of architecture. A system of pools (piscinae) was traced, whose bottoms, covered with mosaics, were placed at varied levels. The southern piscina was probably turned into a storage area during the 6th century, as is indicated by amforae of the types KEAY LIII (LR I) (Pl. 5, Fig. 1 and 2), KEAY LXV (LR II) (Pl. 5, Fig. 3), KEAY XC (Pl. 5, Fig. 4) and KEAY LXIV (Pl. 5, Fig. 5)Sector 3 encompassed the peak of Pupavica hill above Vučipolje, where the existence of architecture from late Antiquity of unknown purpose (a refugium or military lookout) was confirmed (6).All three sectors deserve further excavation, as it will be possible to gain insight into the development of a rural community located along the route of the main roads leading from Salona, the main city of the province of Dalmatia, towards the interior. This fact, along with highly suitable natural conditions for successful agricultural cultivation, offered possibilities of great prosperity to this settlement, for which we now have confirmation that it existed in the period from the 4th – 6th centuries, although an earlier date can also be expected. As the site at which the grave vaults and settlement complex were discovered is called Crkvina ("Church"), traces of early Christian structures can be expected in further investigations.
Keywords: Dugopolje; Roman period; late Antiquity; grave chambers